Designing Soil Color Sensors to Determine Soil Characteristics Based on Internet of Things (IoT) - Andriansyah, Muhammad Afifi; Arifin, Moch; Maroeto, Maroeto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Soil color is the important due to its relation with other soil properties. It is usually analysis with the standard Munsell Soil Color Charts (MSCC). While other properties including organic matter need to be analyzed in the laboratory. The objective of this study is to develop IoT sensor for soil that is able to detect rapidly soil color and other properties including C-organic, pH, and cation exchange capacity (CEC). Soil color data from five soil type was analyzed using the MSCC and used as input data to the IoT (internet of things) sensor. In addition, soil properties obtained from lab tests was also included. The designed IoT sensor was used to detect soil color and soil properties of 7 soil types used as the testing samples. The sensor performance was evaluated by comparing soil properties predicted using IoT and lab analysis. Results showed the use of IoT soil sensor succeeded in determining soil characteristics including pH, CEC, and C-organic based on soil color. In addition, the soil color sensor had high accuracy to predict soil properties with a very small difference compared to the lab analysis, namely 0.01% difference for C-organic, and other properties of <5% difference. The development of IoT soil sensor will be important in the fields of agriculture and land management. Keywords: Acidity (pH), CEC, C-Organic, IoT, Soil Color.